CHARITY FOR OUR FAMILY GODDESS: : The Marwaris And A Caste Association In Colonial India - Tanaka, Tetsuya (The Indonesian Journal of Social Studies, 2025)
This study analyzes the Kedia Sabha (association for the Kedia lineage) as a case study for historical analysis on how an Indian merchant community, known as Marwaris, described themselves through managing a caste association and invented their family goddess through editing their caste journals in colonial India. A historical-ethnographic methodology is used to analyze using caste journals and archival sources. The organization was founded in 1913 as a charitable association with the purpose of supporting members of the lineage residing in Calcutta. The organization has two contrasting characteristics; one is a caste association to promote their social, cultural, and economic welfare for members of a certain lineage or caste, and the other is a charitable institution for the public in theory. First, a review of the literature on caste associations in colonial India and Marwari’s involvement in the caste associations is conducted. The Kedia Sabha is then analyzed as a case study to determine how charity functions as both social consumption and economic accumulation.